Optimum économique et efficience historiographique dans l’Histoire des deux Indes - Muriel Brot (Etudes Epistémè)
Published from 1770 to 1780, Raynal’s Histoire des deux Indes, to which Diderot contributed, questions the legitimacy and usefulness of the colonies, and the best way to retain them and to make them profitable. Raynal and Diderot were equally aware that the reforming power of their work would depend on its didactic force, that promoting an optimal mode of colonisation would require an efficient historiography. As a result, they questioned and opposed each other on the best way to write the history of the Indies. As the search for effectiveness and efficiency appears at all levels of the work, from its conception to its writing, this study analyses the two authors’ divergent historiographical strategies, which led them to open up the field of colonial history to apparently disparate data, thus making it a fundamental economic and political work.